The thermochemical behaviour of thiol collectors and collector mixtures with sulphide minerals - Taguta, Jestos (Department of Chemical Engineering, 2016)
Thiol collectors continue to dominate the base metal sulphide (BMS) and platinum group mineral (PGM) flotation industry. The behaviour of thiol collectors and collector mixtures with sulphide mineral surfaces has been extensively studied using different techniques such as XPS, ToF-SIMS, UV-VIS, etc. However, most of these techniques require a collector dosage above monolayer coverage, take place under equilibrium conditions and may not simulate flotation conditions. Moreover, most of the studies focus on isolated minerals yet exploitable ores exist as an association of sulphide minerals. The use of thiol collector mixtures in the base metal sulphides (BMS) and platinum group mineral (PGM) flotation industries has been reported to offer several performance benefits by many researchers. However, the mechanism whereby these collector mixtures adsorb onto a specific mineral surface is still not clearly understood. This study used isothermal titration microcalorimetry to monitor sub-monolayer reactions by continuously measuring the heats of adsorption as the reactions between thiol collector (and collector mixtures) and sulphide minerals (and mixed minerals) proceed in real time. The enthalpy of adsorption does not only characterise the intensity of adsorption between a collector and mineral surface but also gives insight into the reaction mechanism, whether physisorption (less negative than -40 kJ/mol) or chemisorption (more negative than -40 kJ/mol). Microflotation was also used to determine the hydrophobicity imparted onto the mineral particles as a result of the mineral-collector interactions. Sulphide minerals investigated were chalcopyrite, pyrite, pyrrhotite and galena. Thiol collectors investigated were xanthates of varying chain length (SEX, SIBX, PNBX and PAX) as well as dithiocarbamates (diethyl-DTC and n-butyl DTC) and diethyl-DTP. The current study seeks to gain knowledge of which collector interacts best with which mineral and an understanding of the mechanism behind the reactions. This study also seeks to investigate the performance and adsorption mechanisms when single minerals are interacted with thiol collectors singly and also in a mixture. A better understanding of how to design collector mixtures is to be gained. Furthermore this study seeks to understand the effect of mineral-mineral interactions on thiol collector adsorption and on the floatability of the pure minerals.